Studi Etnobotani Tumbuhan Berpotensi Sebagai Obat Tradisional untuk Penyakit Hipertensi dan Asam Urat di Kecamatan Mowila - Gusti Ayu Kadek Risna Meriyanti; Ikhsan Sidiq; Wa Ode Masrida; Restu Nur Hasanah Haris; Hesti Trisnianti Burhan; Nur Fitriana Muhammad Ali (Jurnal Penelitian Sains dan Kesehatan Avicenna, 2022)
Background: The use of conventional drugs for gout has an impact on increasing blood pressure. Currently the use of herbal medicine is increasing, because it has a very small negative impact compared to conventional medicine. Observations at the Mowila Community Health Center found that people consume decoctions from plant leaves to lower blood pressure and relieve the effects of gout. Objective: This study aims to study plant species that have the potential as traditional medicines for hypertension and gout which have been used empirically by the people of Mowila District. Methods: This research was conducted in 10 villages in Mowila District during April-May 2022 using a descriptive exploratory method with 20 respondents with hypertension and gout who were selected based on secondary data from the Mowila Health Center. Results: The types of plants used as antihypertensive drugs are soursop, salam, katuk, kelor, castor oil, avocado, belimbing wuluh, cat's kumis and Sambiloto contain chemical compounds of flavonoids utilized by boiling the leaves. As for uric acid, they include greetings, cat whiskers, red ginger, bitter, Chinese betel, chlorophylls, pitchers, dadap containing flavonoids and saponins which are utilized by boiling the leaves or rhizomes. Conclusion: The community adopts the way of utilizing herbal plants which are processed traditionally so that they can overcome the diseases they are experiencing, especially hypertension and gout.